Surveillance of central line associated bloodstream infection (CLABSI) - comparison of current (CDC/NHSN) and modified criteria: A prospective study - Durgesh Rai; Pravin Kumar; Poonam Gupta; Pardeep K Verma (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: There is a huge load of central line-associated bloodstream infection (CLABSI) being reported in developing countries, with increased mortality and healthcare costs. Effective surveillance is a must to reduce the incidence of CLABSI. The current criteria (Centre for Disease Control and Prevention/National Healthcare Safety Network [CDC/NHSN]) for CLABSI surveillance have their own shortcomings. For diagnosing CLABSI, current CDC/NHSN CLABSI surveillance criteria are laborious and time consuming with low predictive power. Hence, modified criteria have been postulated, which are simple and implementable at resource-constrained setups. The primary objective was to compare modified criteria with CDC criteria. The secondary objective was to determine the prevalence of CRBSI. Material and Methods: A total of 98 patients with central line in situ or having the central venous line removed ≤24 hrs prior to the date of the event were enrolled. Paired blood cultures were obtained and results were analyzed using differential time to positivity. Results: The incidence of CLBSI was 8.16% and the device utilization rate was 11.6%. The negative predictive value of both the surveillance criteria was found to be excellent and comparable (96.2% for modified criteria and 97.1% for CDC criteria), therefore both can be used for screening purposes. AUC for current CDC/NHSN criteria was better than modified criteria (0.76 versus 0.66, P < 0.0001), suggesting it to be a better criterion for surveillance of CLABSI. Conclusion: Modified criteria were not superior to CDC/NHSN criteria for surveillance. Thus, there is a scope of improving the modified criteria for the purpose of surveillance. CLBSI load was higher; CLABSI bundle for prevention is thus highly recommended.